UNLV Health Sciences Library's Initial Response to the COVID-19 Pandemic: How a Versatile Environment, Online Technologies, and Liaison Expertise Prepared Library Faculty in Supporting Its User Communities. Issue 4 (1st October 2020) - Weeks, Aidy; Houk, Kathryn M.; Nugent, Ruby L.; Corn, Mayra; Lackey, Mellanye
Abstract: In this case study, the University of Nevada, Las Vegas Health Sciences Library describes how a flexible and technology-focused service model, liaison relationships, and individual expertise all contributed towards rapid mobilization of online instruction, virtual library services, and new resources to keep pace with the sudden needs of their user communities in the School of Medicine, School of Dental Medicine and local Las Vegas community prior to and during stay-at-home mandates related to the COVID-19 global pandemic of 2020.